Engage and enjoy–investigating predictors of employee engagement and work satisfaction in equine veterinary professionals - Elte, Yteke; Acton, Kate; Martin, Jessica; Nielen, Mirjam; van Weeren, René; Wolframm, Inga (Frontiers in Veterinary Science, 2023)
Individuals working in the field of veterinary care are regularly affected by their profession. High levels of responsibility to often provide life-saving health care to animals combined with having to manage owners’ expectations and irregular working hours can cause considerable levels of work-related stress among professionals in equine veterinary practice. On the positive side, research also shows that working in the veterinary profession can have a positive impact on personal well-being and feelings of fulfilment. A limited number of studies has investigated work satisfaction and engagement among veterinarians across the globe, and none specifically in the equine veterinary work field. The aim of the current study was to identify relevant predictors of employee engagement and work satisfaction in relation to demographic and work environment related factors in the equine veterinary profession. A cross-sectional study design was used to investigate work satisfaction and employee engagement among equine veterinary professionals from the UK, the US and the Netherlands using an online survey. Results suggest that levels of work engagement and satisfaction in the veterinary profession may be gauged using four factors. These factors encompass Pride and purpose (the extent to which personal core values align with the mission of the employer, i.e. the veterinary practice), Company culture and relationship with management, (the manner in which staff members interact with each other and the management), Working conditions and compensation (formal employment conditions relating to responsibilities and rewards and levels of collegiality) and Team culture and learning possibilities (encouragement to pursue personal and professional growth). Findings underline the importance of being particularly mindful of inexperienced colleagues, those with demanding family commitments and, where feasible, of providing employees with a modicum of autonomy in order to ensure a satisfied equine veterinary workforce.